Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pengguna Jasa PT. ASDP Indonesia Ferry (Persero) di Pelabuhan Kamal - Madura - Kristanto, Andana Haris; Hidayat, Sapit (Universitas Hang Tuah, 2023)
This study aims to determine and analyze the effect of service quality on the level of satisfaction by service users at PT. ASDP Indonesia Ferry (Persero) Kamal Port. Is a quantitative research model simple regression analysis, a sample of 54 respondents, using the formula for the number of unknown population. The data collection instrument used a questionnaire (questionnaire). Data analysis used validity test, reliability test, simple linear regression test, hypothesis test, partial test (t test), processed with SPSS. The results of the validity and reliability tests with rtable 0.279 obtained 20 statement items that were declared valid from service quality and 20 items from statements that were declared valid from customer satisfaction and all items statement reliability. The R test result is 0.004, meaning that service quality affects customer satisfaction by 40%, while 60% is influenced by other variables. Based on the results of the t test, it can be interpreted that the effect of service quality on service satisfaction at PT ASDP Indonesia Ferry (Persero) Kamal Port users with a tcount value of 1.111 ≤ ttable 2.00785.